Specific-locus mutation frequencies in mouse stem-cell spermatogonia at very low radiation dose rates. - Russell, W L (1982)
Experiments were undertaken to augment the information on the lowest radiation dose rates feasible for scoring transmitted induced mutations detected by the specific-locus method in the mouse. This is the type of information most suitable for estimating genetic hazards of radiation in man. The results also aid in resolving conflicting possibilities about the relationship between mutation frequency and radiation dose rate at low dose rates. There was no statistically significant difference between mutation frequencies obtained in spermatogonia with 300 R (1 R = 2.6 x 10(-4) coulombs/kg) of gamma radiation at two different dose rates, 0.005 and 0.0007 R/min, or between either of these frequencies and data obtained earlier at dose rates of 0.8 R/min and below. This supports the view in an earlier publication by one of us (W.L.R.) that, at approximately 0.8 R/min and below, mutation frequency is independent of dose rate. Because this independence is now shown to extend over the more than 1000-fold range from 0.8 to 0.0007 R/min, it seems likely that it would hold at still lower dose rates, perhaps even to the much lower dose rates encountered in most human exposures.